Serum somatomedin and somatomedin generation by the perfused liver in protein malnourished rats - Shapiro, Brahm (Division of Endocrinology and Diabetology, 2018)
The studies presented in this thesis represent an attempt to characterise some aspects of the abnormalities of somatomedin physiology in protein-energy malnutrition. A suitable bioassay to study somatomedin was found in that of Van den Brande and Du Caju (1974) which makes use of uniform discs of cartilage punched from slices of immature porcine costal cartilage. The handling of the cartilage discs was made easy by the specially designed incubation rack. Preincubation increased sensitivity of the cartilage, and post incubation with radioactive tracer reduced the potential interference of varying sulphate content of assay samples. Serum samples were subjected to formal multipoint parallel line bioassay and data analysed by a computer programme designed to examine such assays. The bioassay was found to be sensitive to a concentration of serum of 5% and to have an index precision of less than 0.30 (and usually less than 0.20).